Предмет: Математика,
автор: comf002850
спростіть вираз (2х-3/х²-4х+4х -х-1/х²- 2х): х²- 2 /х³- 4х
Sanya2263:
Прикрепи фотографию задания
Ответы
Автор ответа:
3
Пошаговое объяснение:
(2х-3/х²-4х+4х -х-1/х²- 2х): х²- 2 /х³- 4х = (-4/х² - х): х² -2/х³ -4х = ((-4-х²) / х²): х² -2/х³ -4х = (-4-х²)/х⁴ - 2/х³ -4х = (-4-х²-2х-4х³)/х⁴ = -((4х³+х²+2х+4)/х⁴)
Похожие вопросы
Предмет: Українська мова,
автор: amalia201
Предмет: Українська мова,
автор: Аноним
Предмет: Русский язык,
автор: zanulkao
Предмет: Математика,
автор: ник3096